Easing the adoption of agent-based modelling (ABM) in tourism research. Issue 8 (11th June 2017) - Johnson, Peter; Nicholls, Sarah; Student, Jillian; Amelung, Bas; Baggio, Rodolfo; Balbi, Stefano; Boavida-Portugal, Inês; de Jong, Eline; Hofstede, Gert Jan; Lamers, Machiel; Pons, Marc; Steiger, Robert
Abstract : Agent-based modelling (ABM) is an emerging approach in tourism research. Despite the natural fit between theories of tourism as a complex, interconnected system, and the generative approach supported in ABM, there has been only limited integration within mainstream tourism research. This research letter reports on a recent gathering of tourism ABM researchers to define the main challenges that face the adoption of ABM in tourism research. These include technical, communications, and novelty issues. In response to these challenges, three potential strategies to ease adoption are outlined: education, awareness, and interdisciplinary teams. These findings are framed as a call for increased attention to the fit of ABM within tourism research, and a framework for negotiating constraints to adoption of this technology.